Determination and assessment of essential elements in Acacia Nilotica-a medicinal and folk uses by different analytical methods - Madbouly, Magdy Diab; Salih, Mutaz Ezzeldien; Ahmed Ali, Elmugdad; Kamel, Laila Tosson (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Acacia Nilotica is a good source of several nutrient elements essential for some metabolic processes. The pods of Acacia Nilotica collected from different areas in Sudan have been analysed for 6 minor (Li, Na, K, Mg, Ca, P) and 3 trace (Fe, Zn, Mn) elements by flame photometry and atomic absorption spectrophotometry using the standard addition and calibration curve methods, respectively. The phosphorous, however, was determined U.V. spectrophotometrically using the standard addition method for measurement of the absorbance, at 410 nm of the complex produced by the coupling of meta-molybdate ammonium vanadate with phosphorous. The ash content, density, colour and pH were also determined by standard methods. The results obtained showed that acacia nilotica samples have been found to be especially rich in several nutrient elements such as, K, Fe and P. Concentration of elements are discussed vis-Ã -vis their medicinal/therapeutic uses. Several statistics like PCA and correlation matrix between elements and pH were performed to the dataset in order to distinguish between geogenic enrichment, lithiogenic, and anthropogenic pollution elements found in the pods. The results suggested anthropogenic and geogenic origin of Na, Ca, P, Fe, Zn, Mn, while Li, K, MgÂ  showed lithogenic and/or geogenic origin and was associated and controlled by mixed origin.